An Intrasite Analysis of Agricultural Economy at Early Islamic Caesarea Maritima, Israel - Kathleen M. Forste (Ethnobiology Letters, 2021)
The archaeological site of Caesarea Maritima in modern-day Israel was an important coastal town in the Early Islamic period (c. 636–1100 CE). In this article, I analyze 15 samples of carbonized wood and non-wood macrobotanical remains recovered from two residential neighborhoods to investigate the production and consumption of agricultural plant products. The identified crop and wood taxa are typical for the Mediterranean coast. Wild seeds point to crop cultivation in the vicinity of the site. Plant remains were collected from discrete contexts and are interpreted with associated features and artifacts, revealing cereal processing debris across a series of rooms in a former warehouse. Such a socioeconomic shift in this building, from a storage area to a crop processing space, is detectable by combining this intrasite analysis with the diachronic research previously conducted at the site.